As experiências de profissionais no acolhimento a crianças e adolescentes vítimas de violência sexual: uma contribuição da psicanálise - Ferreira, Isabella de Paula (Universidade Federal de São Carlos, 2022)
The present study has asits theme the experience of professionals who work directly with children and adolescents victims of sexual violence. The main objective is to understand the experiences of social care and psychology professionals in this context, analyzing how the direct work with these patients affects the different areas of their lives. For this, it was proposed to use semi-structured interviews during three meetings. The results were obtained through Bardin's content analysis, based on theoretical contributions from psychoanalysis and contemporary studies on trauma, which produced three categories: countertransference, vicarious traumatization and self-care. It was possible to verify that the professionals are directly impacted by the performance. In the professional activity, the impacts were mainly associated with: the relationship with those responsible for the victims; with the negative feelings that arise during the consultations; with the difficulties present in the legal sphere. With regard to personal life, impacts were found at the interface between professional life and motherhood, which led to changes in the world view. Finally, the importance of support and support from a cohesive and multidisciplinary team to deal with the affections raised by the care of this population was identified. Although the findings cannot be generalized, they are in line with the literature and allow future studies to delve into the creation of training and support projects for different professions that are related to the flow of care for children and adolescents who are victims of sexual violence.
The experiences of professionals in the reception of children and adolescents victims of sexual violence: a contribution of psychoanalysis
Keywords: Violência sexual; Trauma; Contratransferência; Traumatização vicária; Psicanálise; CIENCIAS HUMANAS::PSICOLOGIA::TRATAMENTO E PREVENCAO PSICOLOGICA